Attitude and opinion of Bicycle-Helmet Signal - Pattama Longani (2018)
© Springer-Verlag Berlin Heidelberg 2015. This paper aims to studies the opinion, attitude and compliance of cyclists who ride a bicycle in Chiang Mai city, Thailand, with a Bicycle-Helmet Signal (BHS). The purpose of BHS is to help decreasing accidents for cyclists. The device automatically shows turning signal when cyclists lean their head to the left or right-hand side. The findings are based on a sample size of 30 which were taken from the local cyclists. Two groups have been separated to test the confidence, the group of cyclists using BHS and the other cyclists who use the same road with the first group. The results of five sections of questionnaires have been analyzed and show the quality of BHS. The details of opinions, attitudes and compliance are valuable for the design of BHS which provides safety on the road.